About music, philosophy and science... - Dankowska, Jagna (Interdisciplinary Studies in Musicology, 2018)
The text attempts to answer the question whether musicians need a philosophy of music. The answer to the question of what music contributes to philosophy - a question superordinate in relation to the investigations of the links between philosophy and music - can be formulated clearly, since we find it in the texts of the most prominent representatives of European philosophical thought, including Schopenhauer, whose ideas are discussed in the paper. These issues are also discussed in literature which explores philosophical issues, by such classics of the genre as Thomas Mann and Herman Hesse, whose profound descriptions bring us closer to an understanding of that which music does directly, by expressing spheres beyond words that cannot be expressed otherwise than through music. Karl Popper regards polyphony as the greatest discovery of European culture, and provides evidence of the closeness of science and philosophy. These three levels of approaching the relationship between philosophy and music lead to demonstrating the axiological essence of music, revealed by performers, who make it possible for music to exist to the full in its sonority, unveiling its metaphysical perfection to its listeners.